2011
DOI: 10.1121/1.3514424
|View full text |Cite
|
Sign up to set email alerts
|

Pressure distributions in a static physical model of the uniform glottis: Entrance and exit coefficients

Abstract: Pressure distributions for the uniform glottis were obtained with a static physical model (M5). Glottal diameters of d ¼ 0.005, 0.0075, 0.01, 0.02, 0.04, 0.08, 0.16, and 0.32 cm were used with a range of phonatory transglottal pressures. At each pressure and diameter, entrance loss and exit coefficients were determined. In general, both coefficients decreased in value as the transglottal pressure or the diameter increased. Entrance loss coefficients ranged from 0.69 to 17.6. Use of these coefficients with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…8. However, the large glottal width behavior of the entrance loss coefficients reported there is not much different from unity, and thus we choose F ¼ 1.0 for all of the calculations reported here.…”
Section: Results For Threshold Presssuresmentioning
confidence: 99%
See 3 more Smart Citations
“…8. However, the large glottal width behavior of the entrance loss coefficients reported there is not much different from unity, and thus we choose F ¼ 1.0 for all of the calculations reported here.…”
Section: Results For Threshold Presssuresmentioning
confidence: 99%
“…In many circumstances, 8,10,11,16 an exit coefficient is used to describe pressure recovery, which occurs between the glottal exit and the entrance to the vocal tract. Results presented in Table II of Ref. 8, which were based on pressure distributions 17,18 taken with the physical model M5, showed that the exit coefficients were small in comparison with the entrance loss coefficients, 12 and thus we set the exit coefficient k ex ¼ 0.…”
Section: A Glottal Aerodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Sec. II in the following text, it will be shown that Titze's assumption is reasonable for intermediate and larger glottal widths but that measurements 13,14 of the entrance loss coefficient at small glottal widths show a strong inverse dependence on these widths. To include this physical effect in the surface wave model, one must include an inverse n 0 term in the expression for the entrance loss coefficient as well as a constant term.…”
Section: Introductionmentioning
confidence: 87%